Coster–Kronig and super Coster–Kronig transitions from the Xe 4s core-hole state. Issue 29 (19th July 2022) - Hikosaka, Yasumasa; Fritzsche, Stephan
Abstract : The Coster–Kronig and super Coster–Kronig decays from the 4s core-hole state in xenon are investigated by coincidence detection of all the emitted electrons and product ions, revealing the branching ratios and the subsequent decay pathways. Abstract : Coster–Kronig and super Coster–Kronig transitions from the Xe 4s core-hole state are investigated by coincidence detection of all the emitted electrons and product ions. The branching ratios of the transitions are determined by analyzing the coincidence data and comparing them to calculations. Subsequent decay pathways following these first-step Auger decays are also clarified.